2016
DOI: 10.1080/01635581.2016.1180411
|View full text |Cite
|
Sign up to set email alerts
|

Luteolin Impacts on the DNA Damage Pathway in Oral Squamous Cell Carcinoma

Abstract: Oral squamous cell carcinoma (OSCC) exhibited high chemoresistance to current treatments. Here we aimed at identifying and repositioning approved drugs that could be selectively toxic toward OSCC cells. Through a cell-based drug screening of 1,280 chemical molecules, we selected compounds lethal to oral cancer SCC-25 cells, while sparing normal keratinocyte HaCaT cells. Within the chemical library, the natural flavonoid luteolin was identified as a potent cytotoxic agent against oral cancer cells in vitro, alo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 52 publications
0
15
0
Order By: Relevance
“…Human oral cavity squamous cell carcinoma‐derived cell line HN26, human pharyngeal squamous cell carcinoma‐derived cell line HN30, and immortalized Human Umbilical Vein Endothelial‐derived cell line HUVEC (ea.hy526 cells, ATCC) were grown in Dulbecco's modified Eagle's medium (DMEM, Life Technologies, Courtaboeuf, France) supplemented with 10% fetal bovine serum (FBS, Life Technologies), GlutaMAX, and antibiotics (Life Technologies). Cell lines were expanded in a humidified atmosphere of 5% CO2 at 37°C.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Human oral cavity squamous cell carcinoma‐derived cell line HN26, human pharyngeal squamous cell carcinoma‐derived cell line HN30, and immortalized Human Umbilical Vein Endothelial‐derived cell line HUVEC (ea.hy526 cells, ATCC) were grown in Dulbecco's modified Eagle's medium (DMEM, Life Technologies, Courtaboeuf, France) supplemented with 10% fetal bovine serum (FBS, Life Technologies), GlutaMAX, and antibiotics (Life Technologies). Cell lines were expanded in a humidified atmosphere of 5% CO2 at 37°C.…”
Section: Methodsmentioning
confidence: 99%
“…Human oral cavity squamous cell carcinoma-derived cell line HN26, 8 human pharyngeal squamous cell carcinoma-derived cell line HN30, 8…”
Section: Cell Lines Preparation Of Conditioned Media and Drugsmentioning
confidence: 99%
See 1 more Smart Citation
“…Kasala et al confirmed the antioxidant and antitumor activities of luteolin against benzo(a)pyrene-induced lung carcinogenesis in Swiss albino mice [257]. Tjioe et al identified luteolin as a potent cytotoxic drug against oral squamous cell carcinoma with low toxicity and high efficiency [258]. It remains to mention that chemopreventive and chemotherapeutic effects of luteolin are also contributed to the synergistic effects with other anticancer therapies such as cyclophosphamide, doxorubicin, and NSAID such as celecoxib [259,260].…”
Section: Luteolinmentioning
confidence: 96%
“…Nonetheless, these chemotherapy drugs always induce side effects, such as nausea, vomiting, loss of appetite, decreased immunity, and adverse effects of oral ulcers. Recently, many natural sources [ 33 , 34 , 35 , 36 , 37 ] and traditional medicinal herbs [ 38 , 39 , 40 ] have been studied on OSCC in an effort to mitigate the abovementioned problems, however the solicitation remains incompletely explored. The present study investigated whether PG could have benefits to cause the inhibiting growth of human gingival squamous carcinoma cells (OECM-1) and human tongue cancer (SAS) cell lines by 3-(4,5-Dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay, flow cytometry assay, Western blotting and autophagosome formation assay.…”
Section: Introductionmentioning
confidence: 99%